Direct identification of enteric adenovirus, a candidate new serotype, associated with infantile gastroenteritis. - Johansson, M E (1980)
Two enzyme-linked immunosorbent assay techniques for detection of adenovirus in stools were developed. The first, which is group-specific, detects the 35 established adenovirus types and, in addition, enteric adenoviruses associated with infantile gastroenteritis. The second technique, which is type-specific, selectively detects enteric adenovirus. The efficiency of these techniques was assayed on nine coded stool specimens from Glasgow children. Eight of nine was classified as adenovirus by the group-speicific enzyme-linked immunosorbent assay. The six enteric adenovirus specimens were antigenically distinct from each of the 35 established adenovirus types but not from each other. They are suggested to represent a new adenovirus serotype which appear to be associated with gastroenteritis without clear-cut respiratory symptoms.